Infrastructural Facility and the Students’ Academic Performance - A Critique - Adejompo Stephen Fagbohunka (Indonesian Journal of Geography, 2017)
Abstract: The paper underscores the infrastructural facility and the student’s academic performance in Adekunle Ajasin University, Akungba Akoko, Ondo State, Nigeria. Thirty questionnaires were administered through a systematic sampling technique in each of the six faculties making a total of 180 questionnaires. The paper has found out a positive relationship between the student’s academic performance, power supply and health facilities. However, the internet facilities and transportation facilities were not adequate, whereas water supply was adequate. A test of the impact of infrastructural facility on the student’s academic performance, using a Chi Square statistical technique revealed a significant value of 177.1 at 0.05 % level. The paper recommends that the existing facilities should be upgraded and significantly improved by the government; urgent attention should be given to the development of the internet facilities and transportation sector of the University. Also, private partnership should be encouraged in the infrastructural development of the University.